2015
DOI: 10.5539/res.v7n11p23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training, Compensation and Work Discipline against Employee Job Performance (Studies in the Office of PT. PLN (Persero) Service Area and Network Malang)

Abstract: The purpose of this study is to describe the training variable and to know the simultaneous and partial effects from the variables of training, compensation and work discipline toward the employee work performance of PT PLN (Persero) Malang Service and Network Area.This research is an explanatory research or explanation study, which explain the causal relationship among the variables through the testing of hypotheses. This research is held in the office of PT PLN (Persero) Malang Service and Network Area. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 6 publications
4
13
0
12
Order By: Relevance
“…Asuransi Jiwa Bringin Jiwa Sejahtera (BRIlife). This is in line with the research conducted by Thaief et al (2015) who concludes that compensation ranks in a good level, especially on salary and complementary compensation where the compensation has a significant influence on staff working performance. Furthermore, the result of the research conducted by Widyatmini (2008) shows that competence significantly influences the performance.…”
Section: Hypothesis Testingsupporting
confidence: 90%
“…Asuransi Jiwa Bringin Jiwa Sejahtera (BRIlife). This is in line with the research conducted by Thaief et al (2015) who concludes that compensation ranks in a good level, especially on salary and complementary compensation where the compensation has a significant influence on staff working performance. Furthermore, the result of the research conducted by Widyatmini (2008) shows that competence significantly influences the performance.…”
Section: Hypothesis Testingsupporting
confidence: 90%
“…Sutrisno (2011, p. 86) suggests that discipline indicates a condition or comity that is on the employee to the company rules and regulations. Thus if the rules or regulations that exist in the company are ignored, or often violated, then the employee has a poor work discipline (Thaief et al, 2015). Discipline is a procedure to correct or punish subordinateemplyoees who break the rules and procedures.Discipline of work is essentially the nature of an employee to obey all laws in their place of work.…”
Section: Discipline Of Employeementioning
confidence: 99%
“…The study of Mangkunegara & Waris (2015) was confirmed by the study of Thaief et al (2015) suggesting that training, compensation, and work discipline have a significant influence on performance of the employee of PT PLN Area Malang, both partially and simultaneously. Meanwhile, the findings of Sofyan et al (2016) in the Regional Office of Ministry of Religious Affairs, South Sulawesi Selatan found that there is positive impact between carrier development on performance and work satisfaction of employees.…”
Section: The Influence Of Fingerprint On Work Disciplinementioning
confidence: 74%
“…There are also studies revealing that the work discipline affects the employees performance significantly (Soss, Fording, & Schram, 2011;Thaief, Baharuddin, & Idrus, 2015;Sofyan et al, 2016). In addition, there are also studies finding that discipline punishment is determined by status, talent, compensation, and performance factors (Rosen & Jerdee, 1974).…”
Section: Introductionmentioning
confidence: 99%